2022
DOI: 10.1080/22221751.2021.2024455
|View full text |Cite
|
Sign up to set email alerts
|

Mapping cross-variant neutralizing sites on the SARS-CoV-2 spike protein

Abstract: The emergence of multiple severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) variants of concern threatens the efficacy of currently approved vaccines and authorized therapeutic monoclonal antibodies (MAbs). It is hence important to continue searching for SARS-CoV-2 broadly neutralizing MAbs and defining their epitopes. Here, we isolate 9 neutralizing mouse MAbs raised against the spike protein of a SARS-CoV-2 prototype strain and evaluate their neutralizing potency towards a panel of variants, inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 66 publications
(90 reference statements)
0
26
0
Order By: Relevance
“…The SD1 region targeted by S3H3 is extremely conserved among SARS-CoV-2 variants (Fig. 4f), thus explaining the cross-neutralization ability of S3H3 towards Omicron, Delta and other variants 46 . These findings also suggest a possibility to design SD1-based broad-spectrum SARS-CoV-2 vaccines.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The SD1 region targeted by S3H3 is extremely conserved among SARS-CoV-2 variants (Fig. 4f), thus explaining the cross-neutralization ability of S3H3 towards Omicron, Delta and other variants 46 . These findings also suggest a possibility to design SD1-based broad-spectrum SARS-CoV-2 vaccines.…”
Section: Discussionmentioning
confidence: 99%
“…We found that Omicron could escape three RBD antibodies, including 8D3, S5D2 and 3C1 (refs. 45,46 ). Both 8D3 and S5D2 are class 1 RBD antibodies and they share similar epitopes centred around loop [477][478][479][480][481][482][483][484][485][486][487][488][489] (refs.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations